2001
DOI: 10.1260/0263617011494097
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Tributyl Phosphate on Silica Gel

Abstract: The adsorption behaviour of tributyl phosphate (TBP) on silica gel was studied. It was found that the adsorption isotherm shapes were complicated, being considered as S- and L-type isotherms according to the Giles classification. Adsorption itself was polymolecular and of a physical nature, the first adsorptive layer involving hydrogen bonding between the protons of surface silanol groups and the electron-donating oxygen atom of the adsorbate molecule. Subsequent adsorption layers were formed via van der Waals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The adsorption occurs in the potential range from approximately 0 V up to À 1.3 V vs. SCE. Adsorption of TBP was also reported on silica gel [6], mineral surfaces [7], Amberlite XAD-4 resin [8] and clay [9].…”
Section: Introductionmentioning
confidence: 79%
“…The adsorption occurs in the potential range from approximately 0 V up to À 1.3 V vs. SCE. Adsorption of TBP was also reported on silica gel [6], mineral surfaces [7], Amberlite XAD-4 resin [8] and clay [9].…”
Section: Introductionmentioning
confidence: 79%
“…They call "no bridging" the absence of hydrophilic silica network: "the solvent attaches itself to the surface silanol group of the fumed silica rendering it inactive for further network formation" [ 1 11. Sazanova et al, studying the adsorption of tributyl-phosphate on silica gel, concluded that the first layer adsorbed on the particle is due to the hydrogen bonding between the protons of silanol groups at surface and the electron-donating oxygen atom of the adsorbate molecule [12]. So, it is reasonable that FeP04 over the surface of HSI will changes the network between hydrophilic silica nanoparticles.…”
Section: Steady Flow Measurementsmentioning
confidence: 99%